Peran Media Sosial Dalam Meningkatkan Preferensi Konsumen Mie Samyu Di Kecamatan Pakuniran Kabupaten Probolinggo - dedi junaedi; Anisa Nur Lathifa; Azizatul Fitriyah; Desi Nur Fadilah; Fitri Mardatillah; Nur Wulan Anggraini (New Economy, 2025)
This research discusses the role of social media in increasing consumer preferences for Mie Samyu in the Pakuniran area, Probolinggo Regency. With advances in digital technology, marketing via social media such as Instagram and Facebook has become an important strategy for micro, small and medium enterprises (MSMEs) to interact with customers and build brand awareness. In this context, this research uses the literature review method to analyze three journals that discuss the influence of social media on consumer behavior. The results show that the credibility of influencers on Instagram, interactive features on social media platforms, and content quality greatly influence consumer purchasing decisions. Mie Samyu, which is known for its distinctive taste, has succeeded in utilizing social media to expand market reach and increase customer loyalty. These findings emphasize the importance of adaptive and creative marketing strategies for MSMEs in facing competition in the digital era.